The Role of Parents in Building an Educational Ecosystem that Supports Religious Learning - Tazkiyyatul Imamah; Triono Ali Mustofa (Journal of Educational Sciences, 2026)
Religious education plays a crucial role in shaping children's character, morals, and spirituality. As the first and foremost educators, parents are not only responsible for teaching religious knowledge cognitively but also serve as educators, guides, motivators, facilitators, and role models in daily life. This study aims to explore the role of parents in building an educational ecosystem that supports Islamic religious learning. Using a descriptive qualitative method with a literature review approach, this research analyzes theories and previous studies related to parental involvement in religious education. The findings indicate that parental involvement is significantly influenced by religious awareness, educational background, and the presence of a supportive family and school environment. On the other hand, several obstacles were identified, such as parental busyness, limited religious knowledge, and the influence of digital media. Therefore, collaboration among families, schools, and communities is essential to create a holistic and sustainable religious education ecosystem. This study is expected to serve as a reference for parents, educators, and educational institutions in strengthening the family's role as the foundation for nurturing children's religious character.